Vulnerability of wastewater treatment plants and wastewater pumping stations to earthquakes - Zare, Mohammad Reza; Wilkinson, Suzanne; Potangaroa, Regan (International Journal of Strategic Property Management, 2010)
Earthquakes are the most common natural hazard in New Zealand which can affect lifelines in populated areas. This research takes into account earthquake effects on treatment plants and pumping stations in wastewater systems as a lifeline. Wastewater treatment plants in four earthquake prone areas in New Zealand were selected for the purpose of assessing their vulnerabilities to earthquakes. Results showed that simple upgraded wastewater treatment plants are the most vulnerable type of wastewater treatment plants in New Zealand. Earthquake vulnerability of 45 wastewater pumping stations in 3 earthquake prone cities in New Zealand was also assessed. The assessment proved that non‐structural components are among the most vulnerable parts in wastewater pumping stations. Since structural vulnerability of some wastewater pumping stations is notable, it requires a need for an immediate rehabilitation plan.First Published Online: 10 Feb 2011